Phylogenetic comparative methods improve the selection of characters for generic delimitations in a hyperdiverse Neotropical orchid clade - Bogarín Chaves, Diego Gerardo (2019)
Taxonomic delimitations are challenging because of the convergent and variable nature of phenotypic traits. This is evident in species-rich lineages, where the ancestral and derived states and their gains and losses are difficult to assess. Phylogenetic comparative methods help to evaluate the convergent evolution of a given morphological character, thus enabling the discovery of traits useful for classifications. In this study, we investigate the evolution of selected traits to test for their suitability for generic delimitations in the clade Lepanthes, one of the Neotropical species-richest groups. We evaluated every generic name proposed in the Lepanthes clade producing densely sampled phylogenies with Maximum Parsimony, Maximum Likelihood, and Bayesian approaches. Using Ancestral State Reconstructions, we then assessed 18 phenotypic characters that have been traditionally employed to diagnose genera. We propose the recognition of 14 genera based on solid morphological delimitations. Among the characters assessed, we identified 16 plesiomorphies, 12 homoplastic characters, and seven synapomorphies, the latter of which are reproductive features mostly related to the pollination by pseudocopulation and possibly correlated with rapid diversifications in Lepanthes. Furthermore, the ancestral states of some reproductive characters suggest that these traits are associated with pollination mechanisms alike promoting homoplasy. Our methodological approach enables the discovery of useful traits for generic delimitations in the Lepanthes clade and offers various other testable hypotheses on trait evolution for future research on Pleurothallidinae orchids because the phenotypic variation of some characters evaluated here also occurs in other diverse genera.